Loss of CCAAT-enhancer-binding protein alpha (CEBPA) is linked to poor prognosis in PTEN deleted and TMPRSS2: ERG fusion type prostate cancers - Minner, Sarah; Poos, Alexandra; Rippe, Karsten (The prostate, 2019)
Background The transcription factor CCAAT-enhancer-binding protein alpha (CEBPA) is a crucial regulator of cell proliferation and differentiation. Expression levels of CEBPA have been suggested to be prognostic in various tumor types. Methods Here, we analyzed the immunohistochemical expression of CEBPA in a tissue microarray containing more than 17 000 prostate cancer specimens with annotated clinical and molecular data including for example TMPRSS2:ERG fusion and PTEN deletion status. Results Normal prostate glands showed moderate to strong CEBPA staining, while CEBPA expression was frequently reduced (40%) or lost (30%) in prostate cancers. Absence of detectable CEBPA expression was markedly more frequent in ERG negative (45%) as compared to ERG positive cancers (20%, P < 0.0001). Reduced CEBPA expression was linked to unfavorable phenotype (P < 0.0001) and poor prognosis (P = 0.0008). Subgroup analyses revealed, that the prognostic value of CEBPA loss was entirely driven by tumors carrying both TMPRSS2:ERG fusions and PTEN deletions. In this subgroup, CEBPA loss was tightly linked to advanced tumor stage (P < 0.0001), high Gleason grade (P < 0.0001), positive nodal stage (0.0003), and early biochemical recurrence (P = 0.0007), while these associations were absent or markedly diminished in tumors with normal PTEN copy numbers and/or absence of ERG fusion. Conclusions CEBPA is down regulated in about one third of prostate cancers, but the clinical impact of CEBPA loss is strictly limited to the subset of about 10% prostate cancers carrying both ERG fusion and deletions of the PTEN tumor suppressor. Our findings challenge the concept that prognostic molecular markers may be generally applicable to all prostate cancers.